Prospective Validation of Edinburgh Dysphagia Score as a Triaging Tool beyond the COVID-19 Era. (12th March 2022) - Walton, Hannah B.; McAvoy, Dean; Kalla, Rahul; McAvoy, Norma; Church, Nicholas; Penman, Ian D.; Williams, Andrew; Trimble, Kenneth; Masterton, Gail S. M.; Plevris, John N.; On behalf of EGAR (Edinburgh GI Audit Research) Collaborative,
Abstract : The Edinburgh Dysphagia Score (EDS) was previously developed to identify patients referred to secondary care with dysphagia, who were most likely to have oesophageal cancer. The aim of this study was to use the EDS prospectively during the COVID pandemic to risk stratify patients to either urgent or routine investigation of dysphagia. Between 1 st April and 1 st July 2020, 283 patients were referred to NHS Lothian with dysphagia. An EDS score was calculated utilizing information in the GP referral letter or information gained in a "HOT clinic." Patients with a score ≥ 3.5 were prioritized for investigation under the "urgent suspicion of cancer" pathway. 243 patients underwent investigations. 18 patients were diagnosed with oesophageal cancer, all of whom had an EDS ≥ 3.5 (range 4-10). Approximately one third of patients with dysphagia had a score of <3.5. Using this cut-off, sensitivity was 100% and negative predictive value 100%. This study shows that the EDS can be used prospectively when triaging patients referred to secondary care with dysphagia. The high negative predictive value using the EDS means that patients who have an EDS < 3.5 can be downgraded to a routine waiting list without leading to delays in diagnosing oesophageal malignancy. This will enable faster investigations for patients who remain on the "urgent suspicion of cancer" waiting list. In the age of COVID-19, with increasingly long waiting lists, the EDS is a useful scoring system to identify patients with the greatest need for urgent endoscopy.